2002
DOI: 10.1046/j.1365-8711.2002.05363.x
|View full text |Cite
|
Sign up to set email alerts
|

Afterglow light curves, viewing angle and the jet structure of  -ray bursts

Abstract: Gamma‐ray bursts are often modelled as jet‐like outflows directed towards the observer; the cone angle of the jet is then commonly inferred from the time at which there is a steepening in the power‐law decay of the afterglow. We consider an alternative model in which the jet has a beam pattern where the luminosity per unit solid angle (and perhaps also the initial Lorentz factor) decreases smoothly away from the axis, rather than having a well‐defined cone angle within which the flow is uniform. We show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
471
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(492 citation statements)
references
References 22 publications
17
471
1
3
Order By: Relevance
“…Several modifications have been suggested to explain some of the observed fluctuations, flares, bumps and wiggles. Such modifications may include different density profiles and fluctuations (Wang & Loeb 2000;Ramirez-Ruiz et al 2001;Dai & Lu 2002;, energy injections (Rees & Meszaros 1998;Sari & Mészáros 2000;Granot et al 2003;Björnsson et al 2004;Jóhannesson et al 2006), jets with complex structure (Mészáros et al 1998;Kumar & Piran 2000;Rossi et al 2002), late engine activity (Dai & Lu 1998;Zhang & Mészáros 2002;Ramirez-Ruiz 2004), microlensing (Loeb & Perna 1998;Garnavich et al 2000;Ioka & Nakamura 2001) or dust echoes (Esin & Blandford 2000;Mészáros & Gruzinov 2000;Reichart 2001). Discerning the different scenarios is only possible through the analysis of the SEDs obtained with multiwavelength observations (see Sect.…”
Section: The Physics Of Grbs and Their Environmentsmentioning
confidence: 99%
“…Several modifications have been suggested to explain some of the observed fluctuations, flares, bumps and wiggles. Such modifications may include different density profiles and fluctuations (Wang & Loeb 2000;Ramirez-Ruiz et al 2001;Dai & Lu 2002;, energy injections (Rees & Meszaros 1998;Sari & Mészáros 2000;Granot et al 2003;Björnsson et al 2004;Jóhannesson et al 2006), jets with complex structure (Mészáros et al 1998;Kumar & Piran 2000;Rossi et al 2002), late engine activity (Dai & Lu 1998;Zhang & Mészáros 2002;Ramirez-Ruiz 2004), microlensing (Loeb & Perna 1998;Garnavich et al 2000;Ioka & Nakamura 2001) or dust echoes (Esin & Blandford 2000;Mészáros & Gruzinov 2000;Reichart 2001). Discerning the different scenarios is only possible through the analysis of the SEDs obtained with multiwavelength observations (see Sect.…”
Section: The Physics Of Grbs and Their Environmentsmentioning
confidence: 99%
“…In particular, we assume an opening angle that varies between min 0:05 and max 0:5 (with a power law distribution of the form / 1 ÿ cos s where the index is s ÿ1:5) and an absolute gamma-ray energy per GRB of 5 10 51 erg released in t 10 s, all of which are well within the reasonable ranges of these parameters [57] assuming a uniform jet (see Ref. [58] for alternative jet models).…”
Section: Metals and The Predicted Grb Ratementioning
confidence: 99%
“…Originally E ¼ 2 was suggested ( Rossi et al 2002;Zhang & Meszaros 2002) for a surface energy density that is a power law in the jet off-axis angle, while a Gaussian surface -Scatter plot of E iso vs. E iso; min . On the dotted line E iso ¼ E iso; min .…”
Section: Power-law E Iso Distributionmentioning
confidence: 99%
“…On the other hand, in the universal jet profile model (Rossi et al 2002;Zhang & Meszaros 2002) all jets have the same surface energy density as a function of off-axis angle (the angle from the jet axis), and thus the observed differences in L B or E iso result from the angle v between the jet axis and the line of sight. This model predicts that the energy probability distribution is a power law with index E , where Rossi et al (2002) and Zhang & Meszaros (2002) suggested k ¼ À2, resulting in E ¼ 2, to reproduce the distributions observed by Frail et al (2001), although this was not a firm prediction. A Gaussian surface energy density profile results in E ¼ 1 (Lloyd-Ronning et al 2004).…”
Section: Introductionmentioning
confidence: 99%